Knockout of the Prostaglandin E2 Receptor Subtype 3 Promotes Eccentric Cardiac Hypertrophy and Fibrosis in Mice. (January 2017) - Liu, Shuang; Ji, Yawei; Yao, Jian; Zhao, Xiaodan; Xu, Hu; Guan, Youfei; Breyer, Richard M.; Sheng, Hongzhuan; Zhu, Jianhua
Background: Prostaglandin E2 receptor subtype 3 (EP3), a Gi protein-coupled receptor activated by prostaglandin E2, plays a particular role in cardioprotection. This study aimed to investigate the impact of EP3 deletion on cardiac remodeling and further elucidate the related involvement of possible signaling pathways. Methods and Results: The animals used were EP3 receptor knockout (EP3KO) mice and wild-type (WT) litter mate controls at 16-18 weeks old. The high-resolution echocardiography and weight index indicated that eccentric cardiac hypertrophy might occur in EP3KO mice, which were having worse cardiac function than WT litter mates. Isolated adult myocytes from EP3KO hearts showed spontaneous lengthening. Cardiac fibrosis was observed in EP3KO mice through Masson trichrome staining. The elevated messenger RNA (mRNA) level in matrix genes and the reduced mRNA, protein, and activity levels of matrix metalloproteinase 2 (MMP-2) indicated an increased synthesis and suppressed degradation of matrix collagen in EP3KO mice. The phosphorylation level of extracellular signal-regulated kinase (ERK) 1/2 protein was reduced in the cardiac tissue of EP3KO mice, accompanied by no significant change in the protein level of total ERK1/2, total p38, phospho-p38, glycogen synthase kinase-3β (GSK3β), phospho-GSK3β, and calcineurin (CaN) as well as CaN activity. Conclusion: EP3 knockout in cardiac tissues could induce eccentric cardiac hypertrophy and cardiac fibrosis at 16-18 weeks old. These effects of EP3 knockout might be regulated through inactivating MAPK/ERK pathway and affecting the MMP-2 expression. Overall, PGE2 -EP3 is necessary to maintain the normal growth and development of the heart.